2023
DOI: 10.3390/jrfm16010033
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 105 IT Project Risks

Abstract: The article is aimed at increasing the probability of successful IT project completion by identifying the sources of 105 universal risks as well as establishing cause-and-effect relationships between these risks. The article presents the results of an analysis of 105 risks relevant to IT projects; five of them are commercial risks, 45 are compliance risks and 55 are project risks. Risk analysis was carried out using the 5Why, SWIFT and Harrington coefficients. Based on the results of the analysis, the root cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…However, despite its active development and accumulated knowledge, the implementation of earlier developed tools does not always guarantee the successful achievement of the planned goals in IT projects. As an example, it is worth citing the results of the study by V. Nikolaenko, proving that IT projects are exposed to 105 universal risks, i.e., risks that can materialize in any IT projects, regardless of their scale, complexity, management methods and number of participants [4]. It is also worth mentioning the statistics of Standish Group International, confirming that more than 70% of implemented IT projects in the US and European countries have been recognized as problematic or incomplete [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite its active development and accumulated knowledge, the implementation of earlier developed tools does not always guarantee the successful achievement of the planned goals in IT projects. As an example, it is worth citing the results of the study by V. Nikolaenko, proving that IT projects are exposed to 105 universal risks, i.e., risks that can materialize in any IT projects, regardless of their scale, complexity, management methods and number of participants [4]. It is also worth mentioning the statistics of Standish Group International, confirming that more than 70% of implemented IT projects in the US and European countries have been recognized as problematic or incomplete [5].…”
Section: Introductionmentioning
confidence: 99%
“…As analysis of the works of D. Proenca, J. Estevens, R. Vieira, J. Borbinha, P. Zou, Y. Chen and T. Chan showed, scientists had not reviewed risks, which elimination is carried out with an increase in the level of maturity [34,41]. The maturity model developed by the authors of this article is based on 105 universal risks that are eliminated with the transition to higher levels of maturity [4].…”
mentioning
confidence: 99%
“…Thus, based on the analysis of the nine most popular project management maturity models, it can be concluded that contractors (performers, suppliers) with a high level of project management maturity ensure the successful achievement of planned goals due to the high maturity of employees, the availability of necessary processes, quality documents, a developed corporate culture of project management based on the best group and individual practices, as well as mechanisms that eliminate the materialization of universal and special risks (Nikolaenko and Sidorov 2023). In this regard, it is logical to assume that the project management maturity assessment is a tool for identifying the best contractor (performer, supplier) who can guarantee the creation of the desired product, successfully complete any project and faithfully fulfill all obligations under the contract.…”
mentioning
confidence: 99%
“…Найбільш ризиковими вважаються проєкти ІТ стартапів. V. Nikolaenko, A. Sidorov [4] зазначили, що незалежно від розміру, складності, тривалості, типу та методів управління ІТ-проєкт наражається на 105 ризиків.…”
unclassified
“…Так, Jenes Schmidt [5] визначив фактори та причини, що призводять до провалу ІТ-проєктів, проаналізував послідовність у часі виявлених факторів та причин, а також запропонував рекомендації щодо оцінки ризиків ІТ-проєктів. V. Nikolaenko, A. Sidorov [4] з метою підвищення вірогідності успішної реалізації ІТ-проєкту виявили джерела 105 універсальних ризиків і встановили причинно-наслідкові зв'язки між ними. О. Сметанюк, А. Бондарчук [5] надали характеристику стану розвитку ІТ-галузі в Україні, розкрили особливості системи управління ІТ-проєктами, місце проєкт-менеджера у ній.…”
unclassified